Pembangunan Instalasi Penampungan Air Hujan (IPAH) Untuk Pengurangan Resiko Krisis Air Bersih - Markum; Misdarti; Arumi, Kinasih Citra; Hadi, Alfian Pujian (Universitas Mataram, 2023)
ABSTRACT. Clean water is a major problem for the residents of Lendang Bontong Hamlet, Sekotong Tengah Village, especially when entering the dry season. Expenditures to buy clean water can reach 25% -40% of their daily income. To meet the need for clean water, there is one spring that is usually used by residents, a distance of 0.6 – 1 km from residential areas, but the water quality has not been tested to meet quality standards. The objectives of the rainwater storage installation (IPAH) construction program are to a) provide a rainwater storage installation, b) carry out analysis and simulation of the IPAH's capacity based on the amount of rainfall (CH), and c) form and train groups for sustainable IPAH management. The method used was applying the principle of active participant participation, through observation and workshop methods, involving as many as 25 heads of households, as potential recipients of IPAH receivers. Based on the process of activities carried out, the following conclusions were obtained; First, a 20-unit IPAH was built and handed over to residents of 20 families. Second, based on the shape and size of the roofs of local residents' houses, the results of the analysis of the relationship between CH and IPAH capacity show that the optimal amount of CH that can be accommodated by a water reservoir (1,100 liters) is 25 mm per day, more than that, rainwater will be wasted. to the catchment. Third, an IPAH management group has been formed whose role is to independently maintain the IPAH if problems or damage occur related to the IPAH and absorption wells Keywords: Construction, IPAH, water crisis